Occurrence, health risk of PAHs and the interrelated microbial communities in ‌the sediment of Jinzhou Bay - Lian, Meihua; Yang, Yugang; Li, Yaqi; Yu, Xiaoman (Frontiers in Microbiology, 2025)
Polycyclic aromatic hydrocarbons (PAHs), a class of persistent organic pollutants prevalent in estuarine sediments, were systematically investigated for their spatial distribution, human health risks, and microbial community interactions across selected contamination gradients. Analytical results demonstrated ∑PAH concentrations in sediments ranging from 0.691 to 25.083 mg/kg dry weight, with benzo[a]pyrene toxic equivalents (TEQBaP) exceeding international sediment quality guidelines (ISQGs) at 30% of sampling sites, primarily near anthropogenic emission hotspots. Lifetime carcinogenic risk assessments revealed maximum values of 2.41 × 10−⁵ (children), 1.98 × 10−⁵ (adolescents), and 3.04 × 10−⁵ (adults), with wastewater discharge zones exhibiting both the highest PAH concentrations and population exposure risks. Taxonomic profiling revealed sediment bacterial communities dominated by Proteobacteria, Bacteroidetes and Chloroflexi at the phylum level. The sulfate-reducing genus Desulfobulbus was ubiquitously detected except at upstream reference sites. Multivariate redundancy analysis (RDA) revealed that total nitrogen (TN), total phosphorus (TP), total organic carbon (TOC), sulfur (S), and PAHs concentrations constituted the key variables governing microbial community structure (p < 0.05).